Lateral bearing capacity and failure mode of geosynthetic-reinforced soil barriers subject to lateral loadings. Issue 6 (December 2016) - Yang, Kuo-Hsin; Wu, Jonathan T.H.; Chen, Rong-Her; Chen, Yi-Shou
Abstract: In addition to self-weight and vertical surcharge, geosynthetic-reinforced soil (GRS) structures have recently been used as barriers to resist lateral forces from natural disasters, such as floods, tsunamis, rockfalls, debris flows, and avalanches. The stability of such structures subject to lateral loading is often evaluated using conventional external stability analyses with the assumption that the reinforced soil mass is a rigid body. However, this assumption contradicts the flexible nature of reinforced soil. In this study, finite element (FE) models of back-to-back GRS walls were developed to investigate the performance of GRS barriers subject to lateral loading. The FE analysis results indicated that the failure mode and lateral bearing capacity of GRS barriers depend largely on the aspect ratio ( L/H : ratio of wall width to wall height). When 0.5 < L/H < 1.0, the GRS barriers would fail internally because of internal sliding along the soil–reinforcement interface at the loading side and the active soil failure at the opposite side. When 1.0 < L/H < 3.0, bottom sliding failure would occur along the foundation–reinforcement interface. When L/H > 3.0, passive soil failure would occur within the GRS barriers at the side subject to the lateral force. The ultimate lateral bearing capacity of GRS barriers increased with an increase in L/H : the ultimate lateral capacity factor N L was 1.4–20.1 times K a for L/H = 0.5–3.0. In addition to the effect of L/H, the numerical results indicated that the backfill friction angle ϕ, unit weight γ, and reinforcement vertical spacing S v considerably affected the lateral bearing capacity of GRS barriers. A hypothetical case study of a GRS barrier against a tsunami force is provided, and a viable method using vertical preloaded soil anchors for improving wall lateral capacity is analyzed and discussed.